2005
DOI: 10.1074/jbc.m502041200
|View full text |Cite
|
Sign up to set email alerts
|

Siglec-5 (CD170) Can Mediate Inhibitory Signaling in the Absence of Immunoreceptor Tyrosine-based Inhibitory Motif Phosphorylation

Abstract: Siglec-5 (CD170) is a member of the recently described human CD33-related siglec subgroup of sialic acid binding Ig-like lectins and is expressed on myeloid cells of the hemopoietic system. Similar to other CD33-related siglecs, Siglec-5 contains two tyrosine-based motifs in its cytoplasmic tail implicated in signaling functions. To investigate the role of these motifs in Siglec-5-dependent signaling, we used transfected rat basophil leukemia cells as a model system. Tyrosine phosphorylation of Siglec-5 led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 41 publications
1
74
0
Order By: Relevance
“…Several CD33-related Siglecs have been shown to inhibit activation pathways induced by immunostimulatory receptors (Avril et al, 2005;Crocker et al, 2007). For example, stimulation of Siglec-5 recruited SHP-1 and SHP-2 and efficiently inhibited FcRI-mediated calcium fluxing (Avril et al, 2005). The cytoplasmic tail of Siglec-11 is very closely related to that of Siglec-5 in respect to sequence similarity and conservation of the protein structure (Angata et al, 2002Hayakawa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several CD33-related Siglecs have been shown to inhibit activation pathways induced by immunostimulatory receptors (Avril et al, 2005;Crocker et al, 2007). For example, stimulation of Siglec-5 recruited SHP-1 and SHP-2 and efficiently inhibited FcRI-mediated calcium fluxing (Avril et al, 2005). The cytoplasmic tail of Siglec-11 is very closely related to that of Siglec-5 in respect to sequence similarity and conservation of the protein structure (Angata et al, 2002Hayakawa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that Siglec-11-expressing microglial cells were less toxic to neurons leading to reduced neurite and neuronal cell body loss in microglia-neuron cocultures. Several CD33-related Siglecs have been shown to inhibit activation pathways induced by immunostimulatory receptors (Avril et al, 2005;Crocker et al, 2007). For example, stimulation of Siglec-5 recruited SHP-1 and SHP-2 and efficiently inhibited FcRI-mediated calcium fluxing (Avril et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine phosphorylation of the ITIM can lead to recruitment of Src homology-2-containing tyrosine phosphatase 1 (SHP-1) and SHP-2 tyrosine phosphatases and initiation of inhibitory signaling [12]. Recent studies have raised the possibility that low-level, constitutive recruitment of tyrosine phosphatases by CD33-related siglecs could be important for maintaining a tonic suppression of leukocyte activation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Siglecs are sialic acid-recognizing Ig-superfamily lectins prominently expressed on immune cells (Crocker et al 2012;Varki and Angata 2006). Members of CD33-related Siglecs have been shown to downregulate both innate and acquired immune responses, and this may occur via cytosolic immunoreceptor tyrosine-based inhibitory motifs (ITIMs) residing in the cytoplasmic region of the protein (Avril et al 2005;Ikehara et al 2004;Lajaunias et al 2005;Nicoll et al 2003;Paul et al 2000;Ulyanova et al 1999;von Gunten et al 2005;Zhang et al 2007). We previously suggested that CD33-related Siglecs may antagonize Toll-like receptor (TLR)-mediated inflammatory responses, leading to a reduction in proinflammatory cytokines and increase in the production of an antiinflammatory cytokine (Ando et al 2008).…”
Section: Introductionmentioning
confidence: 99%